(untitled) (Journal of the College of Basic Education, 2022)
In this work presents models and analytical techniques for studying the nature of the doing system of an interrupt-driven kernel due to high packet arrival rate appeared in Gigabit networks. An analytical study is presented describing the effect of high interrupt rate on system performance. The performance is studying in requisites of throughput, latency, and system power. The derived equations of system throughput, latency, system power, and stability condition. The effect of interrupts on system performance had never been denoted to it yet analytically in the past. and this analytical work is the first of its kind. In this work is also using simulation considered both Poisson and bursty traffic with empirical packet size distribution.